Kelayakan Usahatani Dan Pengaruh Biaya Operasional Terhadap Pendapatan Petani Kelapa Sawit Di Kelurahan Tebing Tinggi, Kecamatan Tebing Tinggi, Kabupaten Tanjung Jabung Barat - Asmaida Asmaida; Indra Marpaung; Wiwin Alawiyah (Universitas Batangahari Jambi, 2026)
This study aims to analyze the financial feasibility of oil palm farming and the effect of operational costs on farmers’ income in Tebing Tinggi Village, Jambi Province. A quantitative approach was used with primary data collected from 50 farmers. The analysis included income analysis, feasibility analysis (BCR, BEP, sensitivity), and multiple linear regression. The results indicate that average production was 2,416 kg/month with a price of IDR 2,800/kg, generating revenue of IDR 6,764,800 and income of IDR 4,490,776 per month. The R/C Ratio and BCR of 2.97 indicate that the farming is feasible and profitable. The BEP production of 812 kg and BEP price of IDR 941/kg indicate a high margin of safety. Regression results show that maintenance costs have a negative and significant effect, while harvesting costs have a positive and significant effect on income. The Adjusted R² of 0.920 indicates a strong explanatory model.